Enhanced Selection of Assistance and Explosive Detection Dogs Using Cognitive Measures - MacLean, Evan L.; Hare, Brian (Frontiers in Veterinary Science, 2018)
Working dogs play a variety of important roles, ranging from assisting individuals with disabilities, to explosive and medical detection work. Despite widespread demand, only a subset of dogs bred and trained for these roles ultimately succeed, creating a need for objective measures that can predict working dog aptitude. Most previous research has focused on temperamental characteristics of successful dogs. However, working dogs also face diverse cognitive challenges both in training, and throughout their working lives. We conducted a series of studies investigating the relationships between individual differences in dog cognition, and success as an assistance or detection dog. Assistance dogs (N = 164) and detection dogs (N = 222) were tested in the Dog Cognition Test Battery, a 25-item instrument probing diverse aspects of dog cognition. Through exploratory analyses we identified a subset of tasks associated with success in each training program, and developed shorter test batteries including only these measures. We then used predictive modeling in a prospective study with an independent sample of assistance dogs (N = 180), and conducted a replication study with an independent sample of detection dogs (N = 90). In assistance dogs, models using data on individual differences in cognition predicted higher probabilities of success for dogs that ultimately succeeded in the program, than for those who did not. For the subset of dogs with predicted probabilities of success in the 4th quartile (highest predicted probability of success), model predictions were 86% accurate, on average. In both the exploratory and prospective studies, successful dogs were more likely to engage in eye contact with a human experimenter when faced with an unsolvable task, or when a joint social activity was disrupted. In detection dogs, we replicated our exploratory findings that the most successful dogs scored higher on measures of sensitivity to human communicative intentions, and two measures of short term memory. These findings suggest that that (1) individual differences in cognition contribute to variance in working dog success, and (2) that objective measures of dog cognition can be used to improve the processes through which working dogs are evaluated and selected.